2011
DOI: 10.4012/dmj.2010-152
|View full text |Cite
|
Sign up to set email alerts
|

The grinding efficiency by diamond points developed for yttria partially stabilized zirconia

Abstract: Recently, the use of all-ceramic restorations has increased and been applied for many types of clinical treatment such as bridges which can be made with high strength ceramic material: yttria partially stabilized zirconia (Y-PSZ) employing the CAD/CAM system. Consequently, points that can grind high strength ceramic material effectively are necessary for modifying the shape of restorations or removing them. So in our research, we fabricated new diamond points used to grind Y-PSZ. These points were made by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 7 publications
(7 reference statements)
1
26
0
1
Order By: Relevance
“…As reported previously , it was demonstrated that the cutting efficiency of diamond burs on Zir depended on the grain size. However, even though diamond burs with SC grains were used, an increase of the thickness of Zir significantly decreased the cutting depth.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As reported previously , it was demonstrated that the cutting efficiency of diamond burs on Zir depended on the grain size. However, even though diamond burs with SC grains were used, an increase of the thickness of Zir significantly decreased the cutting depth.…”
Section: Discussionsupporting
confidence: 68%
“…Cutting force was determined according to a previous study conducted by Siegel and von Fraunhofer , who reported that the mean cutting force applied by dentists was 99.3 ± 23.4 g (corresponding to 0.97 ± 0.23 N). The cutting force of about 0.9 N was also used in other studies, in which cutting efficiency was evaluated in relation to dental settings . However, cutting torque was not evaluated and controlled in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Zirconia can be processed by instruments coated with diamond abrasive grains because it has lower hardness than aluminum. It has been reported that higher grindability is achieved with larger diamond grains . However, the surface roughness is increased, so the rotary instrument should be changed sequentially from a large to small grain size of the diamond abrasives of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Zirconia cores are often veneered with glass ceramics to achieve superior esthetics . More recently, monolithic full‐contour restorations have been fabricated using newly developed high‐translucency zirconia . Ceramic restorations routinely require occlusal and contour adjustments, resulting in a rough surface that may cause several problems, such as plaque accumulation, gingival inflammation, wear of the opposing teeth, and reduction of ceramic strength.…”
mentioning
confidence: 99%
“…Ohkuma et al [5] tested diamond burs made by electrodeposition of diamond grains, with a larger diameter (200 µm) than that of traditional points (100 µm) designed to cut high strength ceramic material and found that yttria partially stabilized zirconia could be ground efficiently.…”
Section: Introductionmentioning
confidence: 99%